DISTINGUISHING SHOCKED FROM TECTONICALLY DEFORMED QUARTZ BY THE USE OF THE SEM AND CHEMICAL ETCHING - Gratz A.J.; Fisler D.K.; Bohor B.F. (My University, 1996)
Multiple sets of crystallographically-oriented planar deformation features (PDFs) are generated by high-strain-rate shock waves at pressures of >12 GPa in naturally shocked quartz samples. On surfaces, PDFs appear as narrow (50-500 nm) lamellae filled with amorphosed quartz (diaplectic glass) which can be etched with hydrofluoric acid or with hydrothermal alkaline solutions. In contrast, slow-strain-rate tectonic deformation pressure produces wider, semi-linear and widely spaced arrays of dislocation loops that are not glass filled.Etching samples with HF before examination in a scanning electron microscope (SEM) allows for unambiguous visual distinction between glass-filled PDFs and glass-free tectonic deformation arrays in quartz. This etching also reveals the internal 'pillaring' often characteristic of shock-induced PDFs. This technique is useful for easily distinguishing between shock and tectonic deformation in quartz, but does not replace optical techniques for characterizing the shock features.
Keywords: SCANNING ELECTRON MICROSCOPY; ETCHING; QUARTZ; DEFORMATION; SHOCK METAMORPHISM